Assessment of causal association between differentiated thyroid cancer and disordered serum lipid profile: a Mendelian randomization study - Ma, Qiang; Li, Yu; An, Lijuan; Guo, Liang; Liu, Xiaokang (Frontiers in Endocrinology, 2023)
Background Research has shown that the disordered serum lipid profile may be associated with the risk of differentiated thyroid cancer (DTC). Whether this association reflect causal effect is still unclear. The aim of this study was to evaluate the causality of circulating lipoprotein lipids on DTC. Methods Mendelian randomization (MR) analysis was conducted to evaluate the relationship between the circulating lipoprotein lipids and DTC risk using single-nucleotide polymorphisms (SNPs) from a genome-wide association (GWA) study containing a high-incidence Italian population of 690 cases samples with DTC and 497 controls. Results Univariate and multivariate mendelian randomization analysis demonstrated that ‘total cholesterol’, ‘HDL cholesterol’, ‘apolipoprotein B’ and ‘ratio of apolipoprotein B to apolipoprotein A1’ were correlated with DTC. According to sensitivity analysis, our results were reliable. Furthermore, multivariate analysis revealed that there is no causative association between DTC and any of the many cause factors when they interact with one another, suggesting that there was a deep interaction between the four factors, which could affect each other. Finally, the mechanism of the related effects each other as well as the target genes with significant SNP regulatory effects in DTC was explored by conducting functional enrichment analysis and constructing the regulatory networks. Conclusions We obtained four exposure factors (total cholesterol, HDL cholesterol, apolipoprotein B and ratio of apolipoprotein B to apolipoprotein A1) closely related to DTC, which laid a theoretical foundation for the treatment of DTC.